Mineralogy of a Possible Ancient Lakeshore in the Sutton Island Member of Mt. Sharp, Gale Crater, Mars, From Mastcam Multispectral Images. Issue 10 (6th October 2022) - Haber, James T.; Horgan, Briony; Fraeman, Abigail A.; Johnson, Jeffrey R.; Bell, Jim F.; Rice, Melissa S.; Seeger, Christina; Mangold, Nicolas; Thompson, Lucy; Wellington, Danika; Cloutis, Ed; Jacob, Samantha
Abstract: The Curiosity rover on the Mars Science Laboratory mission has found extensive evidence that Gale crater once hosted a habitable lacustrine environment; however, there are remaining questions about the chemistry and duration of the lake and the nature of the climate at the time. In this study, we use Mastcam multispectral data to investigate the mineralogy of the Sutton Island member of the Murray formation, a part of the basal layers of Mt. Sharp, which consists of heterolithic mudstone and sandstone that are distinct from the finely laminated mudstones that dominate much of the Murray. Sutton Island includes at least one instance of desiccation cracks, indicative of subaerial exposure, and uniquely irregular diagenetic features that may be related to local bedrock permeability. These features suggest that Sutton Island experienced a complex history of deposition and diagenesis which may be crucial for understanding changing water‐rock interactions within Gale. We find that most Mastcam bedrock spectra in this region lack the absorptions associated with hematite found throughout the Murray, and instead show deeper absorptions shifted toward longer wavelengths that are more consistent with Fe‐smectites such as nontronite. Elemental chemistry from ChemCam supports this interpretation, as SiO, MgO, Li, and the chemical index of alteration are elevated in this region. Combined with observations of bedrock sedimentology, this suggests that Sutton Island was deposited in a nearshore or low stand environment, and we hypothesize that the clay minerals were produced in this region due to sub‐aerial exposure and weathering in a semi‐arid climate. Plain Language Summary: The Curiosity rover on the Mars Science Laboratory mission has found extensive evidence that Gale crater once hosted a habitable lake environment; however, there are remaining questions about the chemistry and timing of the lake and the nature of the climate at the time. In this study, we use Mastcam data to investigate the composition of the Sutton Island member of the Murray formation, which consists of mixed fine and coarse grained rocks that are distinct from the very fine‐grained rocks that dominate much of the Murray. Sutton Island includes mudcracks, indicative of surface exposure, and irregular alteration features that may be related to local bedrock differences. These features suggest that Sutton Island experienced a complex history of deposition and alteration which may be crucial for understanding changing water‐rock interactions within Gale. We find that most bedrock in this region lack features associated with hematite found throughout the Murray, and instead show features that are more consistent with clay minerals. Combined with observations of mudcracks and chemistry data, this suggests that Sutton Island was deposited in a nearshore environment, and we hypothesize that the clays were produced in this region due to surface exposure and weathering in a semi‐arid climate. Key Points: Mastcam multispectral data in Sutton Island exhibit bands >900 nm consistent with Fe/Mg‐clay minerals like nontronite Sutton Island was deposited in a lowstand/nearshore environment and exposed to more subaerial weathering than the nearby Murray The presence of abundant clay minerals in Sutton Island significantly reduced fluid flow and alteration during later diagenesis